2021
DOI: 10.1016/j.jhsg.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Surgical Interventions for Trapeziometacarpal (Thumb Base) Osteoarthritis: A Systematic Review

Abstract: This systematic review (SR) aimed to identify the surgical interventions available for trapeziometacarpal osteoarthritis and document their efficacy on pain, physical function, psychological well-being, quality of life, treatment satisfaction, and/or adverse events. Methods: This PROSPERO-registered SR's protocol was developed based on the Cochrane intervention review methodology and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results: Among 9049 potential studies identified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 103 publications
(392 reference statements)
0
9
0
Order By: Relevance
“…If patients do not respond to a prolonged comprehensive conservative treatment, including splinting, physiotherapy, anti-inflammatory drugs and change of lifestyle, surgical procedures can be considered. The standard procedure is simple trapeziectomy with ligament reconstruction (Hamasaki et al., 2021; Yeoman et al., 2019). However, trapeziectomy can be associated with reduction of thumb length due to proximal migration of the first metacarpal bone, which may lead to loss of grip and pinch strength (Yang and Weiland, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…If patients do not respond to a prolonged comprehensive conservative treatment, including splinting, physiotherapy, anti-inflammatory drugs and change of lifestyle, surgical procedures can be considered. The standard procedure is simple trapeziectomy with ligament reconstruction (Hamasaki et al., 2021; Yeoman et al., 2019). However, trapeziectomy can be associated with reduction of thumb length due to proximal migration of the first metacarpal bone, which may lead to loss of grip and pinch strength (Yang and Weiland, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…treatment is a successful treatment strategy for CMC-1 OA, which, on average, reduces pain and improves hand function. 7,8 Moreover, in a large cohort with a mean follow-up of 2.2 years, only 15% of the patients underwent further surgery. 9 Treatment outcomes such as pain relief and functional improvement have been frequently studied; however, in recent days there is increasing attention for the patients' interpretation of their treatment outcomes.…”
mentioning
confidence: 99%
“…We assumed no effect on outcome, so we chose the dorsal approach, for the purpose of avoiding awareness of study group allocation. However, recently Hamasaki et al. (2021) have shown that the dorsal approach is largely inferior to trapeziectomy by an anterior approach in terms of treatment satisfaction and reducing the number of adverse events.…”
Section: Discussionmentioning
confidence: 99%